Analisis Faktor-faktor yang Memengaruhi Produksi Padi Sawah di Desa Kemuja Kecamatan Mendo Barat Kabupaten Bangka - Ananda, Inka Ayu; Agustina, Fournita; Muntoro, Muntoro (Universitas Galuh, 2025)
Kemuja Village, West Mendo District, Bangka Regency is one of the rice paddy production centers in the Bangka Belitung Islands Province because Kemuja Village has a potential rice field area to be cultivated with a land area of 344 ha. However, rice cultivation in Kemuja Village faces problems in the form of suboptimal rice production. This research aims to: (1) find out the amount of rice production in Kemuja Village, West Mendo District, Bangka Regency, (2) analyze the factors that affect rice production in Kemuja Village, West Mendo District, Bangka Regency. Using the survey method, data was obtained from 30 respondents of paddy rice farmers in Kemuja Village, West Mendo District, Bangka Regency who were selected through purposive sampling. The data in this study were analyzed quantitatively using the descriptive method and multiple regression of the Cobb-Douglass production function model. The results of the study show that (1) the average amount of rice production in Kemuja Village, West Mendo District, Bangka Regency in one planting season is 1,283 kg. (2) the factors that affect rice production in Kemuja Village, West Mendo District, Bangka Regency are seeds (X1), urea fertilizer (X3), NPK fertilizer (X4), and pesticides (X5).